A MC‐based anthropomorphic test case for commissioning model‐based dose calculation in interstitial breast 192‐Ir HDR brachytherapy - Peppa, Vasiliki; Thomson, Rowan M.; Enger, Shirin A.; Fonseca, Gabriel P.; Lee, Choonik; Lucero, Joseph N. E.; Mourtada, Firas; Siebert, Frank‐André; Vijande, Javier; Papagiannis, Panagiotis (Medical physics (Lancaster), 2023)
Purpose To provide the first clinical test case for commissioning of 192Ir brachytherapy model‐based dose calculation algorithms (MBDCAs) according to the AAPM TG‐186 report workflow. Acquisition and Validation Methods A computational patient phantom model was generated from a clinical multi‐catheter 192Ir HDR breast brachytherapy case. Regions of interest (ROIs) were contoured and digitized on the patient CT images and the model was written to a series of DICOM CT images using MATLAB. The model was imported into two commercial treatment planning systems (TPSs) currently incorporating an MBDCA. Identical treatment plans were prepared using a generic 192Ir HDR source and the TG‐43‐based algorithm of each TPS. This was followed by dose to medium in medium calculations using the MBDCA option of each TPS. Monte Carlo (MC) simulation was performed in the model using three different codes and information parsed from the treatment plan exported in DICOM radiation therapy (RT) format. Results were found to agree within statistical uncertainty and the dataset with the lowest uncertainty was assigned as the reference MC dose distribution. Data Format and Usage Notes The dataset is available online at http://irochouston.mdanderson.org/rpc/BrachySeeds/BrachySeeds/index.html,https://doi.org/10.52519/00005. Files include the treatment plan for each TPS in DICOM RT format, reference MC dose data in RT Dose format, as well as a guide for database users and all files necessary to repeat the MC simulations. Potential Applications The dataset facilitates the commissioning of brachytherapy MBDCAs using TPS embedded tools and establishes a methodology for the development of future clinical test cases. It is also useful to non‐MBDCA adopters for intercomparing MBDCAs and exploring their benefits and limitations, as well as to brachytherapy researchers in need of a dosimetric and/or a DICOM RT information parsing benchmark. Limitations include specificity in terms of radionuclide, source model, clinical scenario, and MBDCA version used for its preparation.